Identification of the plastic zone using digital image correlation (Fracture and Structural Integrity, 2014)
In this paper Digital Image Correlation (DIC) is used to study the evolution of the plastic zone close to a crack tip. A modified CT-specimen was used in order to fulfill the plane stress condition. The strain field around the crack tip was measured using two cameras and stereo DIC, so that out-of-plane movements are taken into account. Then, the Virtual Fields Method was used to identify the plastic zone, looking at the parts of the specimen which deviates from the linear elastic behavior. With such approach, it was possible to individuate the onset of plasticity close to the crack tip and follow its evolution. A comparison with FEM results is also provided.
Keywords: Virtual Fields Method